FOSTERING PROSPERITY: APPLYING HUMAN VALUES THROUGH MALAYSIA'S NATIONAL EDUCATION PHILOSOPHY IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 (International Journal of Food and Nutritional Sciences, 2022)
Human values continue to influence individuals and society in spite of the difficulties posed by the Fourth Industrial Revolution. It is provided via education, which is the primary means of producing value. The "National Education Philosophy" of the Malaysian government is an excellent tactic to instill strong human values with the community's academic dominance without being overtaken by rapid development. Healthy human values in all spheres of life— physical, According to the poll, among intellectual elements, respondents gave priority to epistemology. The study's conclusions on the nuanced impacts of the "National Education Philosophy" of the Malaysian government on participants' viewpoints and values establish the groundwork for further investigations into educational tactics and the formation of allencompassing human values in various communities. emotional, spiritual, and intellectual—are what Malaysia seeks to foster and advance. The research looks at participants' opinions on applying human principles drawn from the National Education Philosophy. In the framework of a flourishing Malaysia, it also evaluates the degree of community respect for these principles. Using an online survey platform, 112 tertiary students from a variety of backgrounds participated in the pilot study, which was carried out in the Klang Valley. The research discovered that a successful existence may be created by human values. The majority of respondents prioritized maintaining their physical health, which is essential for overall wellbeing, along with environmental concerns and leading a clean lifestyle. According to the study, the majority of respondents showed strong emotional stability whether dealing with their own, others', or the world's issues. According to the study, respondents' personal rights and demands are valued more highly than those of their families, communities, and nations.